GENISTEIN AND DAIDZEIN, IN COMBINATION, PROTECT CELLULAR INTEGRITY DURING 7,12-DIMETHYLBENZ[A]ANTHRACENE (DMBA) INDUCED MAMMARY CARCINOGENESIS IN SPRAGUE-DAWLEY RATS - Pugalendhi, Pachaiappan; Manoharan, Shanmugam; Suresh, Kathiresan; Baskaran, Nagarethinam (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
The status of glycoconjugates (protein bound hexose, hexosamine, sialic acid and fucose) in plasma or serum serve as potential biomarkers for assessing tumor progression and therapeutic interventions. Aim of the present study was to investigate the protective effect of two major soy isoflavones, genistein and daidzein, in combination on the status of glycoconjugates in plasma, erythrocyte membrane and mammary tissues during 7,12-dimethylbenz[a]anthracene (DMBA) induced mammary carcinogenesis in female Sprague-Dawley rats. A single subcutaneous injection of DMBA (25 mg rat-1) in the mammary gland developed mammary carcinoma in female Sprague-Dawley rats. Elevated levels of plasma and mammary tissue glycoconjugates accompanied by reduction in erythrocyte membrane glycoconjugates were observed in rats bearing mammary tumors. Oral administration of genistein + daidzein (20 mg + 20 mg kg-1 bw/day) to DMBA treated rats significantly (p< 0.05) brought back the status of glycoconjugates to near normal range. The present study thus demonstrated that genistein and daidzein in combination protected the structural integrity of the cell surface and membranes during DMBA-induced mammary carcinogenesis.